The Digital Literacy for Personal Data Protection - Ginting, Lisna Wati (Sultan Agung Notary Law Review, 2025)
In the digital era, personal data has become one of the most valuable assets, yet its protection remains a critical issue. As digital platforms continue to proliferate across sectors such as the economy, governance, and social interactions, the collection and processing of personal data have raised concerns regarding privacy violations, identity theft, and data misuse. Digital literacy, which includes both technical proficiency and awareness of data protection, is essential in safeguarding personal data and mitigating these risks. This literature study explores the role of digital literacy in protecting personal data, with a particular focus on Indonesia, where internet usage is rapidly increasing, but digital literacy and data privacy awareness remain underdeveloped. By reviewing relevant studies and regulations, this study highlights the importance of digital literacy as a tool for empowering individuals to make informed decisions about their data and recognize the risks associated with digital interactions. The study also examines strategies for enhancing digital literacy, such as integrating data privacy education into curriculums and increasing public awareness through media campaigns. Ultimately, this research underscores the need for a comprehensive, multifaceted approach to improving digital literacy, which can help build a safer digital ecosystem and protect individuals' personal data in an increasingly connected world.